Double whammy: the genetic variants in CECR2 and high Hcy on the development of neural tube defects - Bai, Baoling; Jiang, Qian; Liu, Lingyun; Liu, Changyun; Zhang, Qin (Frontiers in Genetics, 2023)
Introduction: Neural tube defects (NTDs) are serious congenital malformations. The etiology of NTDs involves both genetic and environmental factors. Loss of CECR2 in mice has been shown to result in NTDs. Our previous study indicated that high homocysteine (HHcy) levels could further reduced the expression level of CECR2. This investigation aims to explore the genetic influence of the chromatin remodeling gene, CECR2, in humans and determine if HHcy can have a synergistic effect on protein expression. Methods: We conducted Next-Generation Sequencing (NGS) of the CECR2 gene in 373 NTD cases and 222 healthy controls, followed by functional assay application to select and evaluate CECR2 missense variants and subsequent Western blotting to identify protein expression levels. Results: From the analysis, we identified nine rare, NTD-specific mutations within the CECR2 gene. Significantly, four missense variants (p.E327V, p.T521S, p.G701R, and p.G868R) were selected via functional screening. The E9.5 mouse ectodermal stem cell line NE-4C, transfected with plasmids expressing p.E327V, p.T521S, p.G868R variants or a recombinant harboring all four (named as 4Mut), exhibited notable reductions in CECR2 protein expression. Furthermore, exposure to homocysteine thiolactone (HTL), an extremely reactive homocysteine metabolite, amplified the reduction in CECR2 expression, accompanied by a significant increase in the apoptotic molecule Caspase3 activity, a potential NTD inducer. Importantly, folic acid (FA) supplementation effectively counteracted the CECR2 expression decline induced by CECR2 mutation and HTL treatment, leading to reduced apoptosis. Discussion: Our observations underscore a synergistic relationship between HHcy and genetic variations in CECR2 concerning NTDs, thereby reinforcing the concept of gene-environment interaction phenomena in NTD etiology.